2017
DOI: 10.1186/s12880-017-0179-7
|View full text |Cite
|
Sign up to set email alerts
|

Automatic MRI segmentation of para-pharyngeal fat pads using interactive visual feature space analysis for classification

Abstract: BackgroundObstructive sleep apnea (OSA) is a public health problem. Detailed analysis of the para-pharyngeal fat pads can help us to understand the pathogenesis of OSA and may mediate the intervention of this sleeping disorder. A reliable and automatic para-pharyngeal fat pads segmentation technique plays a vital role in investigating larger data bases to identify the anatomic risk factors for the OSA.MethodsOur research aims to develop a context-based automatic segmentation algorithm to delineate the fat pads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
(26 reference statements)
0
6
0
7
Order By: Relevance
“…Adequate CPAP treatment can increase pulmonary ventilation and ameliorate the inflammation of arteries in patients with OSAS (9). Patients show improvements in blood oxygen concentration on the first day following CPAP treatment, and further benefits are observed during an extended course of treatment (10). The molecular and immunological mechanisms underlying this type of therapy are a major concern when selecting CPAP in patients with OSAS.…”
Section: Introductionmentioning
confidence: 99%
“…Adequate CPAP treatment can increase pulmonary ventilation and ameliorate the inflammation of arteries in patients with OSAS (9). Patients show improvements in blood oxygen concentration on the first day following CPAP treatment, and further benefits are observed during an extended course of treatment (10). The molecular and immunological mechanisms underlying this type of therapy are a major concern when selecting CPAP in patients with OSAS.…”
Section: Introductionmentioning
confidence: 99%
“…Bariatric surgeries are associated with anatomical changes in the body due to weight loss. Studies [3,4,5] suggested changes in upper airway dimensions and decrease parapharyngeal pad of fat in obese subjects after acute weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Shahid et al, [3] studied the effect of weight loss on the pharynx dimensions. They examined the patients (after weight loss) by a low-dose CT scan of the upper airway using a 16-slice scanner.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to polysomnography, magnetic resonance images are also obtained to analyze upper airway anatomy. The segmentation algorithm proposed by Shahid et al 41 is applied on more than 400 images to extract different biomedical features from the images. In total, we get more than 50 quantitative and categorical features to analyze and study the pathogenesis of OSA.…”
Section: Studying the Pathogenesis Of Osamentioning
confidence: 99%